In-situ photochemical synthesis of Au nanoparticles in polymer matrix with one-component thioxanthone disulfide for detection of benzene, toluene and xylene vapours - Cinko, Tugce; Koyuncu, Umut; Omur, Birsel Can; Altindal, Ahmet; Arsu, Nergis (ELSEVIER SCIENCE SA, 2019)
Thioxanthonation of diphenyl units of diphenyl disulfide was achieved successfully. The photoreduction and photostabilization ability of 2, 2'-disulfanediylbis (9H-thioxanthen-9-one) was used for in-situ preparation of Au nanoparticles either in solution or in poly(ethylene glycol) methyl ether acrylate / poly(ethylene glycol) diacrylate polymer matrix. SPR(Surface Plasmon Resonance) absorption band of formed Au NPs were recorded at 550 nm by UV-vis spectroscopy. Indeed, formation of elliptical shaped nanoparticles (4-8 gm) as well as spherical ones (11-14 nm) in nanocomposite films were obtained depending on UV irradiation time. DLS (Dynamic Light Scattering) measurements also changed from 440 nm to about 200 nm as a function of irradiation time. The potential of Au NPs/ polymer nanocomposite film as a sensing element for benzene, toluene, xylene (BTX) sensing was studied at different temperatures. An overall evaluation of the experimental results showed that Au NPs/ polymer nanocomposite film has good potential as a sensing element for the detection of BTX vapours.
Keywords: Gold nanoparticle/polymer nanocomposites; Thioxanthone disulfide; Photopolymerization; Gas sensors; SENSING PROPERTIES; GOLD NANOPARTICLES; CATALYSTS; NOBLE; Chemistry; Materials Science